Kreativitas Tutor Dalam Mengembangkan Media Pembelajaran Pada Program Paket B Di PKBM Mendawai Palangka Raya Kalimantan Tengah (Journal Pendidikan Ilmu Pengetahuan Sosial, 2020)
The researcher aims to find out the tutor's creativity in developing learning media and the obstacles encountered in its development in the Mandawai Palangka Raya PKBM package B program. While the approach used is a qualitative approach using observation, interview and documentation guidelines. Based on observations and interviews, it turned out that the creativity of the tutor in developing learning media in the PKBM B package program was not optimal, and as a result the quality of education was still far from what was expected, as evidenced by the low interest of the community to include their children in the education program. Obstacles experienced by tutors in developing learning media, that learning citizens lack focus on learning on the subject matter being taught but are only interested in the media used, in addition generally citizens learn to be passive when the learning process takes place, another thing that is an obstacle is the number of media there is still less when compared to the number of citizens learning so learning is not optimal. Based on the description above, it can be concluded (1) tutors in the program are not creative enough in developing learning media, that is, they still depend on the media distributed by the government (2) obstacles faced by tutors in developing learning media are the lack of supporting media and the ability of tutors who are still lacking in developing learning media. The researcher aims to find out the tutor's creativity in developing learning media and the obstacles encountered in its development in the Mandawai Palangka Raya PKBM package B program. While the approach used is a qualitative approach using observation, interview and documentation guidelines. Based on observations and interviews, it turned out that the creativity of the tutor in developing learning media in the PKBM B package program was not optimal, and as a result the quality of education was still far from what was expected, as evidenced by the low interest of the community to include their children in the education program. Obstacles experienced by tutors in developing learning media, that learning citizens lack focus on learning on the subject matter being taught but are only interested in the media used, in addition generally citizens learn to be passive when the learning process takes place, another thing that is an obstacle is the number of media there is still less when compared to the number of citizens learning so learning is not optimal. Based on the description above, it can be concluded (1) tutors in the program are not creative enough in developing learning media, that is, they still depend on the media distributed by the government (2) obstacles faced by tutors in developing learning media are the lack of supporting media and the ability of tutors who are still lacking in developing learning media.